Clasificación de parásitos de la malaria (2024)
Malaria, a prevalent parasitic disease, has traditionally been diagnosed through microscopic blood examination, a method that requires considerable expertise and is subject to interpretative variability. This project proposes the use of advanced image processing techniques and machine learning to enhance the detection and classification of the four malaria parasites that infect humans: Plasmodium falciparum, P. vivax, P. ovale, and P. malariae.